Regeneration Behaviour of Important Tree Species in Relation to Disturbance in Joint Forest Management Adopted Village-Forests in Satpura Plateau, Madhya Pradesh, India - Pande, P. K. (Indian Forester, 2006)
Regeneration behavior and population structure of important tree species were analyzed in nine village forests under Joint Forest Management in East Chhindwara Forest Division (Madhya Pradesh). Possible future composition changes in these forests were explored. The greater contribution of seedlings, saplings and individuals in lower diameter-class for sites-I, III, VII and IX showed ’extending population structure’, which is indicative of better regeneration on these sites. However, sites-VI, VIII and II were highly disturbed sites, the proportion of individuals were greater in larger diameter-classes as compared to smaller diameter-classes. This is indicative of ’decline population structure. Present and past disturbances adversely affect the regeneration and composition of different tree species at different sites. Besides the protection of these forests, artificial regeneration is suggested for the improvement of tree regeneration and maintenance of vegetation composition in near future.